The Roles of Brand Image, E-Recommendation Label, and Social Influence on Purchase Decision of TransNusa's Air Tickets on Traveloka's Platform: A Mediating Analysis of Trust - Petan, Fredik Alexander; Harwani, Yuli (Dinasti International Journal of Digital Business Management, 2024)
This research aims to find out and analyze the roles of brand image, e-recommendation label, and social influence on purchase decisions of TransNusa air tickets on Traveloka's platform, with trust as a mediating variable. A quantitative approach was employed by an online survey of 150 respondents of TransNusa's passenger who purchase the tickets via Traveloka platform. The collected data was analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). Results indicate that brand image significantly influence purchase decisions. While e-recommendation label insignificantly influences purchase decision. However, social influence does not influence purchase decision. Trust partially mediates the relationships between brand image, e-recommendation label, social influence and purchase decisions. The findings contribute to the understanding of online purchase behavior, emphasizing the crucial role of trust in shaping consumer purchase decisions. This research provides valuable insights for TransNusa airlines seeking to enhance their marketing strategies.